A High-Fidelity Simulation Platform for Industrial Manufacturing by Incorporating Robotic Dynamics Into an Industrial Simulation Tool - Zhang, Zengjie; Dershan, Ram; Enayati, Amir M. Soufi; Yaghoubi, Marjan; Richert, Dean; Najjaran, Homayoun (IEEE robotics and automation letters, 2022)
Simulation provides an efficient and safe evaluation solution for industrial automation to pretest software before deploying it in real systems. However, only high-fidelity simulation environments that precisely reconstruct the behavioral patterns of real systems can guarantee a successful transfer from simulation to reality (sim-to-real). Many existing industrial simulation tools provide libraries for various industrial devices, which simplify the development efforts significantly, but they generally lack the ability to model the system dynamics and often fail to generate a realistic representation when the system performance is sensitive to the modeling deviation. For example, robots equipped with intelligent algorithms potentially lead to task failure if the software is sensitive to the variation of the system dynamics. In this paper, we design a novel simulation platform for industrial manufacturing use cases consisting of a cooperative robot and a modular manufacturing device. With the dynamic model of the robot integrated into a manufacturing digital-twining software, the platform achieves high simulation fidelity by incorporating the effect of the robot dynamics to the control logic of the industrial tasks. Also, the simulation can exchange data with the real robot via an open protocol, which enables the simultaneous test of the real and simulated systems. Two experiments are conducted on the simulation platform to validate its fidelity in terms of the consistent control logic with the real system. Also, a workpiece distribution use case is studied to show how the simulation platform is used to develop a task-planning algorithm for a manufacturing application.